Strengthening Islamic Education Through Majelis Raodhatul Khairat: A Case Study of Muslim Women's Nonformal Learning - Darmawan, Abdi; Elya; Zaitun (Letiges, 2025)
This study aims to explore the mechanisms of integrating educational activities and nonformal factors to achieve the maximum success of Majelis Raodhatul Khairat in strengthening Islamic education for Al-Khairat Muslim women in South Tinggede Village, despite operating with limited formal resources. The Research employs a qualitative approach with a single-case study design, data collection through participatory observation, in-depth interviews, and documentation, as well as interactive model-based data analysis. The findings reveal that the majelis implements a holistic educational mechanism through the integration of four activities: recitation, yasinan, maulid, and funeral bathing training that address cognitive, spiritual, affective, and psychomotor dimensions in a balanced manner with strategies of Material contextualization, cyclical learning, and tiered development. Maximum success is supported by the synergy of ten nonformal factors: strong emotional bonds, transformative leadership, program flexibility, participatory learning, cultural support, social solidarity, nonformal incentive systems, program continuity, the use of simple technology, and alignment of vision with congregation aspirations, which interact within an organic learning ecosystem. The Research generates theoretical findings that social capital and the synergy of contextual factors are more determinative of the success of community-based nonformal Islamic education than the fulfillment of formal prerequisites, such as a rigidlya , structured curriculum and academically highly qualified teaching personnel. Implications for the SDGs include providing a replicable model of quality inclusive education (Goal 4), women's empowerment (Goal 5), and reduction of educational access disparities (Goal 10), demonstrating that community-based nonformal education can serve as an effective solution for sustainable development.